Chlorovirus and myovirus diversity in permafrost thaw ponds - Culley, Alexander; Lovejoy, Connie; Comte, Jérôme; Vincent, Warwick F.; Lévesque, Alice V. (Aquatic Microbial Ecology, 2020)
Permafrost thaw ponds occur in high abundance across the northern landscape of Canada and are sites of intense microbial activity, resulting in carbon dioxide and methane emissions to the atmosphere. In this study, we focused on viruses as largely unstudied agents of top-down control in these high-latitude microbial ecosystems. Specifically, we compared the diversity of myovirus, chlorovirus and host microbial communities in an organic soil palsa valley pond and a mineral soil lithalsa valley pond. These 2 subarctic permafrost landscapes are both common in northern Québec, Canada. Sequence analysis of ribosomal small subunit RNA genes showed that the community structure of bacteria and microbial eukaryotes differed significantly between the 2 ponds, which both differed from microbial communities in a rock-basin lake (whose formation was not related to permafrost thawing and which we used as a reference pond) in the same region. The viral assemblages included 439 OTUs in the uncultured Myoviridae category and 41 OTUs in the family Phycodnaviridae. Phylogenetic analysis of the latter based on an amino acid sequence alignment revealed a single large clade related to chloroviruses, consistent with the abundant presence of chlorophytes in these waters. As there was for the bacterial and eukaryotic communities, there were also significant differences in the community structure of these viral groups among the 3 ponds. These results suggest that host community composition is influenced by environmental filtering, which in turn contributes to driving viral diversity across landscape types.